Application of genomics-assisted breeding for generation of climate resilient crops: progress and prospects - Kole, Chittaranjan; Muthamilarasan, Mehanathan; Henry, Robert; Edwards, David; Sharma, Rishu; Abberton, Michael; Batley, Jacqueline; Bentley, Alison; Blakeney, Michael; Bryant, John; Cai, Hongwei; Cakir, Mehmet; et al. (Frontiers in Plant Science, 2015)
Climate change affects agricultural productivity worldwide. Increased prices of food commodities are the initial indication of drastic edible yield loss, which is expected to surge further due to global warming. This situation has compelled plant scientists to develop climate change-resilient crops, which can withstand broad-spectrum stresses such as drought, heat, cold, salinity, flood and submergence, and pests along with increased productivity. Genomics appears to be a promising tool for deciphering the stress responsiveness of crop species with adaptation traits or in wild relatives towards identifying underlying genes, alleles or quantitative trait loci. Molecular breeding approaches have been proven helpful in enhancing the stress adaptation of crop plants, and recent advancement in next-generation sequencing along with high-throughput sequencing and phenotyping platforms have transformed molecular breeding to genomics-assisted breeding (GAB). In view of this, the present review elaborates the progress and prospects of GAB in improving climate change resilience in crop plants towards circumventing global food insecurity.